Pengaruh Lingkungan Sekolah dan Self Efficacy terhadap Minat Melanjutkan Pendidikan Ke Perguruan Tinggi Dengan Status Sosial Ekonomi Orang Tua Sebagai Variabel Moderasi - Violeni Qurata Ayuni; Eko Wahjudi (Universitas PGRI Madiun, 2021)
This study aims to determine the effect of the school environment and self-efficacy on the interest in continuing education to higher education with the socioeconomic status of parents as a moderating variable. The population were students of class XII SMA Negeri 1 Dolopo. Sampling was done by purposive sampling and obtained a sample of 105 students. Data collection was carried out using an online questionnaire via google form. The hypothesis tested using Structural Equation Modeling (SEM) modeling, using the WarpPLS approach. The results showed that (1) the school environment had no effect on the interest in continuing education to higher education, (2) self-efficacy had a significant effect on the interest in continuing education to higher education, (3) the socioeconomic status of these parents was not a variable that was able to moderate the influence of the school environment on the interest in continuing education to higher education. and (4) the socioeconomic status of parents is not a variable that can moderate the effect of self-efficacy on the interest in continuing education to higher education